Pengembangan Media Lecture Maker pada Pembelajaran Fisika di MTsN Model Padang - Elvisa, Gita Oktia; Hurriyah, Hurriyah; Sari, milya (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2018)
This development aims to generate and develop Lecture Maker produc in Lessons that meet valid, practical and effective eligibility criteria. This research is a type of research development or Research and Development (R & D) with procedural model adapting 4-D models that define, design, develop and disseminate. Data were obtained from questionnaires given to 2 media experts, 2 material experts, 1 linguist, 2 educators and 40 students. Based on the average result from the validation test by 5 validators by 91%, from the practicality test by 2 teachers got 77% result, from the practical test by 40 students got 80% result and the effectiveness test by 40 students got the result of 78% Therefore, it can be concluded that the Lecture Maker is feasible to be used as a medium of learning that meets the criteria of validity, practicality, and effectiveness and can increase learning interests of learners.